Orofacial EMG in Congenital Multiple Cranial Neuropathies - Rao, Vamshi K. (Pediatr Neurol Briefs, 2015)
Investigators from Armand-Trousseau hospital and University of Paris studied 90 infants aged birth to 6 months with multiple cranial nerve involvement.